"Those foreigners ruin everything here": Interactional functions of ethnic labelling among pupils in the Netherlands1. (10th May 2019) - van de Weerd, Pomme
Abstract: This paper contributes to a deeper understanding of ethnic labelling practices by examining their interactional functions among secondary school pupils in Venlo, the Netherlands. Pupils with migration backgrounds often labelled themselves and others "Turk, " "Moroccan, " or "foreigner, " and labelled others "Dutch." The paper highlights that ethnic labelling can be understood not only as identity construction, but also as interactional work. I build on membership categorization analysis (MCA), complemented by conversation analysis (CA), to analyse how pupils' use of ethnic labels evoked an expert role which altered interactants' power positions; and how, often, pupils engaged in jocular mockery with ethnic labels and in that way mitigated the effects of exclusionary and stigmatizing discourses about people with migration backgrounds. Finally, I argue that pupils' labelling practices had locally occasioned meanings and functions, but that they ultimately reflect wider‐spread systems of categorization and marginalization of people with migration backgrounds in the Netherlands. Abstract : Dit artikel draagt bij aan een dieper begrip van etnisch labelen door de interactionele functies hiervan te analyseren onder middelbare scholieren in Venlo, Nederland. Leerlingen met een migratieachtergrond labelden zichzelf vaak "Turk, " "Marokkaan, " of "buitenlander, " en labelden anderen "Nederlander." Het artikel benadrukt dat etnisch labelen niet alleen als identiteitswerk begrepen kan worden, maar ook als interactioneel werk. Ik gebruik membership categorization analysis (MCA), aangevuld door conversatie analyse (CA), om te analyseren hoe leerlingen de rol van expert aannamen door te refereren naar een label, en daarmee interactionele machtsposities omkeerden; en hoe leerlingen vaak etnische labels gebruikten in schertsende plagerijen, en daarmee stigmatiserende discoursen over mensen met een migratieachtergrond becommentarieerden. Ik beargumenteer dat het labelen door leerlingen lokaal geïnformeerde betekenissen en functies had, maar dat dit uiteindelijk wijder verspreide categorisering en marginalisatie van mensen met migratieachtergronden in Nederland weerspiegelt.